2021
DOI: 10.1007/s10554-021-02493-9
|View full text |Cite
|
Sign up to set email alerts
|

Additional value of left atrium remodeling assessed by three-dimensional echocardiography for the prediction of atrial fibrillation recurrence after cryoballoon ablation

Abstract: Cryoballoon ablation (CBA) is a safe and efficient therapeutic option for atrial fibrillation (AF). However, AF recurrence occurs in 25% of the patients, leading to repeated ablations and complications. Previous reports have shown that left atrium (LA) assessed by M-Mode and two-dimensional echocardiography (2DE) predicts AF recurrence. Nevertheless, these methods imply geometrical assumptions of the LA remodeling, which is a three-dimensional process. We hypothesized that LA remodeling by three-dimensional ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
0
1
Order By: Relevance
“…Although there are several papers demonstrating the impact of AF on LA remodeling as well as the utility of LA size and function on AF recurrence prediction ( 29 31 ), our study shows that patients with PerAF had a higher degree of LA anatomical remodeling and functional impairment than that in patients with PAF, reflecting different stages of the disease. Moreover, LA reservoir strain could be a useful indicator in estimating cardiac function remodeling induced by AF even before LA volume dilation and showed better discriminative value than LAEF to separate AF from sinus rhythm patients.…”
Section: Discussioncontrasting
confidence: 67%
“…Although there are several papers demonstrating the impact of AF on LA remodeling as well as the utility of LA size and function on AF recurrence prediction ( 29 31 ), our study shows that patients with PerAF had a higher degree of LA anatomical remodeling and functional impairment than that in patients with PAF, reflecting different stages of the disease. Moreover, LA reservoir strain could be a useful indicator in estimating cardiac function remodeling induced by AF even before LA volume dilation and showed better discriminative value than LAEF to separate AF from sinus rhythm patients.…”
Section: Discussioncontrasting
confidence: 67%
“…Multiple studies have identified that a larger LA diameter [ 16 , 17 , 18 , 19 ] and volume [ 7 , 15 , 20 , 21 ] measured via transthoracic echocardiography before CA are associated with a higher probability of AF recurrence. Moreover, the LA volume index, calculated by dividing LA volume by body surface area, including the maximum, mean, minimum, and volume index, was relevant to AF recurrence after CA [ 22 , 23 , 24 ]. Studies have reported a significantly higher LA volume index in patients with AF relapse, attributing to the association between AF recurrence and poor LA structural remodeling [ 22 , 23 , 24 ].…”
Section: Use Of Echocardiography For the Prediction Of Af Recurrence ...mentioning
confidence: 99%
“…Moreover, the LA volume index, calculated by dividing LA volume by body surface area, including the maximum, mean, minimum, and volume index, was relevant to AF recurrence after CA [ 22 , 23 , 24 ]. Studies have reported a significantly higher LA volume index in patients with AF relapse, attributing to the association between AF recurrence and poor LA structural remodeling [ 22 , 23 , 24 ]. A growing series of studies also claim an independent relationship between functional indices, such as left ventricular (LV) and LA ejection fraction, and the ratio of mitral inflow velocity to mitral annular tissue velocity (E/e’) and AF recurrence after CA [ 16 , 19 , 25 , 26 ].…”
Section: Use Of Echocardiography For the Prediction Of Af Recurrence ...mentioning
confidence: 99%
See 1 more Smart Citation